Analisis Perencanaan Pajak Melalui Penyusutan Aktiva Tetap untuk Menghitung Pajak Penghasilan (PPh) Badan - Agustini, Sri; Kamaliyah, Fithrah (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The aim of this research is to find out the difference between straight-line and double-declining depreciation methods in determining profit that will affect the tax burden, so that good and efficient tax planning can be carried out by CV. Yan's Jaya. This study uses a descriptive quantitative method with data collection techniques using secondary data derived from the financial reports of CV. Yan's Jaya. The results of this study are the calculation of depreciation using the straight-line method used for depreciation of buildings while vehicles and office inventory use the declining balance depreciation method. There are differences in the calculation of depreciation of fixed assets, the use of depreciation rates and costs incurred when acquiring fixed assets, where the depreciation expense according to the company shows a smaller value than the depreciation expense according to the applicable tax regulations. There are differences in profit margins that do not reflect actual income. The implication of this research is that CV. Yan's Jaya can carry out tax planning, especially in the depreciation of fixed assets in accordance with the applicable tax laws.